The Impact of E-Billing Adoption and Tax Regulation Understanding on Individual Taxpayer Compliance: The Moderating Role of Tax Socialization - Lulu Nur Fadhilah; Abdurrahman Maulana Yusuf (FEB Universitas Mulawarman, 2025)
This study examines the relationship between e-Billing adoption, understanding of tax regulations, and individual taxpayer compliance within a regional tax administration context. Primary data were collected from 100 individual taxpayers registered as e-Billing users at KPP Pratama Samarinda Ilir and analyzed using PLS-SEM. The results show that e-Billing adoption and taxpayers’ understanding of tax regulations are positively associated with taxpayer compliance. Tax socialization also demonstrates a direct association with compliance; however, its moderating role is not statistically supported. This finding suggests that tax socialization tends to operate independently, consistent with the Theory of Planned Behavior’s view of social influence as a direct determinant. Given the use of cross-sectional and self-reported data from a single tax office, the findings are associative and context-specific rather than causal